Disrupted resting-state insular subregions functional connectivity in post-traumatic stress disorder. Issue 27 (July 2016) - Zhang, Youxue; Xie, Bing; Chen, Heng; Li, Meiling; Guo, Xiaonan; Chen, Huafu
Abstract : Abstract: Post-traumatic stress disorder (PTSD) is suggested to be a structural and functional abnormality in the insula. The insula, which consists of distinct subregions with various patterns of connectivity, displays complex and diverse functions. However, whether these insular subregions have different patterns of connectivity in PTSD remains unclear. Investigating the abnormal functional connectivity of the insular subregions is crucial to reveal its potential effect on diseases specifically PTSD. This study uses a seed-based method to investigate the altered resting-state functional connectivity of insular subregions in PTSD. We found that patients with PTSD showed reduced functional connectivity compared with healthy controls (HCs) between the left ventral anterior insula and the anterior cingulate cortex. The patients with PTSD also exhibited decreased functional connectivity between the right posterior insula and left inferior parietal lobe, and the postcentral gyrus relative to HCs. These results suggest the involvement of altered functional connectivity of insular subregions in the abnormal regulation of emotion and processing of somatosensory information in patients with PTSD. Such impairments in functional connectivity patterns of the insular subregions may advance our understanding of the pathophysiological basis underlying PTSD.